Skylight application for natural lighting in a Building; The University of Tehran Branch of Melli Bank case study - Nasersharifi, Y. (EDP Sciences, 2014)
This study investigated the quality and potential lighting energy savings in a bank building retrofitting project in Tehran by using solar passive lighting. The retrofitting scenarios are based on OFFICE project findings. Despite the increase in occupancy and service quality of the bank after retrofitting, the peak electricity consumption significantly decreased (approximately 20). The results showed that even the proper solar passive lighting in most of day hours had been enough to satisfy the existing building luminance before retrofitting due to the initial passive design of the building, however, by retrofitting and improving the lighting system using skylight and artificial lighting the quality of lighting increased meaningfully to cover the standards of lighting for precision activities required for banking. Â© 2014 Owned by the authors, published by EDP Sciences.